Beetle diversity in fragmented thornscrub and isolated trees - Cuéllar Rodríguez, Luis Gerardo; Jurado, Enrique; Flores, Joel (2017)
Abstract Due to land use change mainly for induced agriculture, Tamaulipan thornscrubin northeast Mexico has been cleared and transformed into small patches of vegetation as small as isolated trees surrounded by agricultural fields. In this study, we explored how tree isolation or growing inside a fragment of remnant vegetation influence diversity of coleopterans in two plant species (Prosopis laevigata (Humb. &Bonpl.exWilld.) M.C. Johnst. (mesquite) and Ebenopsis ebano (Berl.) Barneby (Texas ebony). We found 72 coleopteran morphospecies; fifteen occurred mainly in remnant fragments and ten mainly in isolated trees. There were more insects under isolated mesquites than under those immersed in remnant fragments, while in Texas ebony the highest beetle density for isolated trees coincided with periods of bean and maize in surrounding agriculture. Keywords: coleopterans, vegetation-patches, landscape